Human splenic polymorphonuclear myeloid‐derived suppressor cells (PMN‐MDSC) are strategically located immune regulatory cells in cancer. Issue 12 (2nd September 2020) - Tavukcuoglu, Ece; Horzum, Utku; Yanik, Hamdullah; Uner, Aysegul; Yoyen‐Ermis, Digdem; Nural, Safa K.; Aydin, Busra; Sokmensuer, Cenk; Karakoc, Derya; Yilmaz, Kerim Bora; Hamaloglu, Erhan; Esendagli, Gunes
Abstract: In contrast to the mouse, functional assets of polymorphonuclear myeloid‐derived suppressor cells (PMN‐MDSC) in the human spleen remain to be better elucidated. Here, we report that the spleen in gastric and pancreatic cancer adopts an immune regulatory character, harbors excessive amount of PMN‐MDSC, and anatomically enables their interaction with T cells. Compared to the peripheral blood, the spleen from cancer patients contained significantly higher levels of low‐density PMN‐MDSC, but not early‐stage MDSC (e‐MDSC) and monocytic‐MDSC (M‐MDSC). Low‐density fraction of polymorphonuclear (PMN) cells was enriched in immature myeloid cells and displayed higher levels of CD10, CD16, and ROS than their blood‐derived counterparts. They were also positive for PD‐L1, LOX‐1, and pSTAT3. The white pulp and periarteriolar lymphoid sheath (PALS) were strategically surrounded by PMN cells that were in contact with T cells. Unlike those from the blood, both low‐density and normal‐density PMN cells from the human spleen suppressed T cell proliferation and IFN‐γ production. Independent of clinical grade, high PMN‐MDSC percentages were associated with decreased survival in gastric cancer. In summary, our results outline the immune regulatory role of the spleen in cancer where neutrophils acquire MDSC functions and feasibly interact with T cells. Abstract : In cancer, the human spleen serves as a reservoir for myeloid‐derived suppressor cells (MDSC), especially PMN‐MDSC. Comparative analyses revealed functional and phenotypic similarities and distinctions between the splenic PMN‐MDSC and the circulating PMN‐MDSC. The spleen has a critical immune regulatory role in cancer patients.